The relationship between psychological well-being and empathy quotient - Amirhesam Khajeh; Ghafar Baharloo; Fatemeh Soliemani (Management Science Letters)
This paper investigates the relationship between psychological well-being and empathy quotient among 200 married students, 100 female and 100 make, in city of Najafabad, Iran. The study uses a questionnaire with 84 questions for measuring psychological well-being, which consists of six parts including Autonomy, Environmental mastery, Personal growth, Positive relation with others, Purpose in life and Self-acceptance, each with 14 questions. Cronbach alphas for these six items were calculated as 0.83, 0.86, 0.85, 0.88, 0.88 and 0.91, respectively. In order to measure empathy quotient (EQ), the study uses EQ-short form, which consists of 22 questions. Cronbach alpha has been calculated as 0.93, which is well above the minimum acceptable level of 0.70. Using stepwise regression technique, the study determines a positive and meaningful relationship between EQ and psychological well-being.